Fixed Point Theory and the Ulam Stability - Janusz Brzdęk; Liviu Cădariu; Krzysztof Ciepliński (Journal of Function Spaces)
The fixed point method has been applied for the first time, in proving the stability results for functional equations, by Baker (1991); he used a variant of Banach's fixed point theorem to obtain the stability of a functional equation in a single variable. However, most authors follow the approaches involving a theorem of Diaz and Margolis. The main aim of this survey is to present applications of different fixed point theorems to the theory of stability of functional equations, motivated by a problem raised by Ulam in 1940.